Are the times changing enough? Print media trends across four decades. (May 2019) - Biscomb, Kay; Matheson, Hilary
Media analysis is an established area of sport sociology which has been documented by researchers systematically since the 1980s. Despite the extent and breadth of the area there have been some methodological trends which include a focus on print media, the analysis of both quantitative and qualitative content, and the analysis of the portrayal of female athletes. This study presents a unique analysis of four decades, from 1984 to 2014, of British print media covering the same two week summer period in six national newspapers, in order to assess whether societal and cultural changes have been reflected in the predominantly patriarchal domain of sport.Outcomes have been mixed, but overall it is clear that there is continued under-representation of female athletes and, that what were once considered to be the major British summer sports (athletics, cricket, golf, tennis) have been replaced by a dominance of soccer reporting. . We provide an overview of the trends documented during the last four decades and offer some insight into the growth of the 'gossip sheets' for men.